Phytochemical Screening and Antioxidant Activity Test of Ethanol Extract of Nelambosuon (Rubiaceae) Leaves Using the DPPH Method - Natalia Aksamina Sagisolo; Ratih Arum Astuti; Wahyuni Watora; A.M. Muslihin (Sean Institute, 2026)
Indonesia is recognized as one of the world’s megabiodiversity countries, possessing a vast diversity of medicinal plants that have long been utilized in traditional medicine. Nelambo suon (Rubiaceae) is an indigenous plant traditionally used by the Tehit Imian tribe in South Sorong, Southwest Papua, for treating wounds, skin infections, and inflammatory conditions. However, scientific information regarding its phytochemical profile and antioxidant activity remains limited. This study aimed to evaluate the phytochemical constituents and antioxidant activity of the ethanol extract of Nelambo suon leaves using the DPPH method. Fresh, undamaged green leaves were dried at room temperature without direct sunlight and extracted by maceration using 96% ethanol. Phytochemical screening was performed to identify major secondary metabolites, while antioxidant activity was assessed using the DPPH free radical scavenging assay and expressed as IC₅₀ values. The phytochemical screening revealed the presence of flavonoids and tannins in the ethanol extract, whereas alkaloids, saponins, steroids, and terpenoids were not detected. The antioxidant assay demonstrated a concentration-dependent increase in radical scavenging activity. The ethanol extract of Nelambo suon leaves exhibited an IC₅₀ value of 83.7 µg/mL, indicating strong antioxidant activity. These findings suggest that Nelambo suon leaves are a promising source of natural antioxidants, likely attributed to their flavonoid and tannin contents. This study provides preliminary scientific evidence supporting the traditional use of Nelambo suon and highlights its potential for further development as a natural antioxidant agent in pharmaceutical and herbal product applications.